Some new Sobraliae from Costa Rica and Panama - Dressler, Robert L. (2013)
A new species of Elleanthus: E. carinatus and three new species of Sobralia: S. fragilis, S. geminata from Costa Rica and S. sotoana from Panama are described and illustrated.